Disruptive Bricolage: Indigenous Politics, Development and Migration in Guatemala - Nichols, Briana (Ethnologies, 2021)
For many indigenous communities in the western highlands of Guatemala, transnational migration is considered critical to community survival. This paper analyzes how extreme migration enables new strategies of social formation and community governance for those who remain. My work builds on the scholarship of “afterlives” that calls for an examination of how historical trajectories embed themselves in contemporary social, cultural, and institutional configurations. Migration can productively be considered in terms of its afterlives. Through this frame, I illustrate how indigenous community members navigate conflicting ideologies of work, progress, and development as they collaborate with non-governmental organizations to support migration prevention initiatives. I argue that community members strategically draw on the Mayan cosmovision to contest western knowledge paradigms of development while simultaneously attending to the demands of external institutional legibility, and in so doing create novel formations of collective governance.